Cardiac function and autonomic cardiac function during a multi-stage cycling event: a brief report - Menard, Vincent; Barrero, Anna; Lachard, Thibault; Robinault, Lucien; Li, Lingxia; Schnell, Frederic; Carré, François; Le Douairon Lahaye, Solène (Frontiers in Sports and Active Living, 2024)
Prolonged and repeated exercise performed during ultra-endurance event can induce general and cardiac fatigue known as exercise-induced cardiac fatigue (EICF). Our objective was to find a possible correlation between the cardiac function and the autonomic cardiac function. During a multistage ultra-endurance event, a female well-trained cyclist underwent daily rest echocardiography and HRV measurements to assessed cardiac function and cardiac autonomic function. Athlete completed 3345km at 65% of her maximum heart rate and 39% of her maximum aerobic power. A progressive improvement of the systolic function for both the left ventricle and right ventricle was observed during the event. Alterations were observed on cardiac autonomic function with an imbalance between sympathetic and parasympathetic but there is no sign of significant correlation between the cardiac function and the autonomic cardiac function and no signs of cardiac fatigue either. Further analysis should be performed on a larger sample to confirm these results.